2022
DOI: 10.1007/s10549-022-06732-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in breast cancer treatment during the COVID-19 pandemic: a Dutch population-based study

Abstract: Purpose We aimed to compare (1) treatments and time intervals between treatments of breast cancer patients diagnosed during and before the COVID-19 pandemic, and (2) the number of treatments started during and before the pandemic. Methods Women were selected from the Netherlands Cancer Registry. For aim one, odds ratios (OR) and 95% confidence intervals (95%CI) were calculated to compare the treatment of women diagnosed within four periods of 2020: pre-COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Indeed, one UK study demonstrated that alterations to breast cancer management were implemented in nearly 60% of patients, and many surgical interventions were substituted with ‘bridging’ endocrine therapy [12]. In the Netherlands neo-adjuvant endocrine therapies for breast cancer increased by 339% during lockdown [13]. As well as reduced availability of surgical resources, radiotherapies and hospital beds, concern that chemotherapy-induced immunosuppression would increase risk for COVID-19 complications may have influenced clinicians’ decisions to switch patients to alternative therapies [14].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one UK study demonstrated that alterations to breast cancer management were implemented in nearly 60% of patients, and many surgical interventions were substituted with ‘bridging’ endocrine therapy [12]. In the Netherlands neo-adjuvant endocrine therapies for breast cancer increased by 339% during lockdown [13]. As well as reduced availability of surgical resources, radiotherapies and hospital beds, concern that chemotherapy-induced immunosuppression would increase risk for COVID-19 complications may have influenced clinicians’ decisions to switch patients to alternative therapies [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the evidence regarding the impact of COVID-19 on treatment decisions for other types of cancer remains inconclusive. While some studies report a significant reduction in the use of adjuvant therapy [ 19 ], others indicate an increase in neoadjuvant therapy options [ 20 ]. The levels of evidence in these studies are not yet sufficient and do not yet allow to draw robust conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In the pre-COVID period, fewer patients received chemotherapy (25.2% vs. 27.0%, p = .04). 489 (13) 1123 (13) 298 (12) 2609 ( 13) 977 ( 13) 1486 ( 14) 549 ( 14)…”
Section: Initial Treatmentsmentioning
confidence: 99%
“…[8][9][10][11] In patients with breast cancer, changes in treatments mainly included changes in the sequence of treatments. 12,13 No delays in initial treatment were found for any of the above mentioned cancers.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation